2019
DOI: 10.1186/s12882-019-1590-9
|View full text |Cite
|
Sign up to set email alerts
|

Arg913Gln variation of SLC12A3 gene is associated with diabetic nephropathy in type 2 diabetes and Gitelman syndrome: a systematic review

Abstract: BackgroundDiabetic nephropathy is a global common cause of chronic kidney disease and end-stage renal disease. A lot of research has been conducted in biomedical sciences, which has enhanced understanding of the pathophysiology of diabetic nephropathy and has expanded the potential available therapies. An increasing number of evidence suggests that genetic alterations play a major role in development and progression of diabetic nephropathy. This systematic review was focused on searching an association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…predominately located in the ion-translocation pathway, the EC domain, the TM-TM and TMcytosol interfaces, and the NT and CT domains, likely affecting NCC folding and stability [20,55,56]. In vitro functional characterization of NCC missense mutations associated with GS revealed defective NCC plasma membrane expression, localization, and activity [57,58].…”
Section: Mutations Associated With Human Diseasesmentioning
confidence: 99%
“…predominately located in the ion-translocation pathway, the EC domain, the TM-TM and TMcytosol interfaces, and the NT and CT domains, likely affecting NCC folding and stability [20,55,56]. In vitro functional characterization of NCC missense mutations associated with GS revealed defective NCC plasma membrane expression, localization, and activity [57,58].…”
Section: Mutations Associated With Human Diseasesmentioning
confidence: 99%
“…Presently, the mechanism of GS with DN is still unclear, and some scholars have proposed that the dysfunction of NCC may be one of the main reasons for the risk of DN due to chronic hyperglycemia caused by insulin resistance in individuals with Type 2 Diabetes [ 9 , 10 ]. In addition, Arg913Gln variation of SLC12A3 gene is associated with DN in type 2 diabetes and GS [ 11 ]. A patient with GS and nephrotic syndrome was reported, the renal pathology revealed minimal lesions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…variation of SLC12A3 gene is associated with DN in type 2 diabetes and GS [11]. A patient with GS and nephrotic syndrome was reported, the renal pathology revealed minimal lesions [7].…”
mentioning
confidence: 96%
“…Bioinformatics analysis showed that if the wild-type 904Arg was replaced by the mutant allele 904Gln, the three-dimensional structure of the SLC12A3 protein will change significantly, and the Arg904Gln mutation may have important physiological significance [ 40 ]. Tanaka et al believed that the Arg904Gln gene variation in SLC12A3 could reduce the risk of diabetic nephropathy in type 2 diabetes mellitus (T2DM) [ 41 ]; however, other studies have provided evidence supporting the correlation between Arg904Gln variant and the disease development of diabetic nephropathy in patients with T2DM and GS, suggesting that this variant may be a key predictor of end-stage renal disease [ 42 , 43 ]. Several suspected pathogenic mutations were found near our newly discovered heterozygous mutant of Asp839Val (c.2516A>T): C.2490C>T (p.Thr830=), c.2495A>G (p.Asp832Gly), c.2532G>A (p.Trp844Ter), c.2510_2511del (p.Leu836_Phe837insTer), c.2514C>T (p.Asp838=), c.2521G>A (p.Gly841Ser), c.2533del (p.Leu845fs), and c.2546T>A (p.Leu849His) ( https://www.ncbi.nlm.nih.gov/clinvar ).…”
Section: Discussionmentioning
confidence: 99%